2009
DOI: 10.1074/jbc.m807191200
|View full text |Cite|
|
Sign up to set email alerts
|

Melittin, a Major Component of Bee Venom, Sensitizes Human Hepatocellular Carcinoma Cells to Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-induced Apoptosis by Activating CaMKII-TAK1-JNK/p38 and Inhibiting IκBα Kinase-NFκB

Abstract: Promoting apoptosis is a strategy for cancer drug discovery. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) induces apoptosis in a wide range of malignant cells. However, several cancers, including human hepatocellular carcinoma (HCC), exhibit a major resistance to TRAIL-induced cell death. Melittin, a water-soluble 26-amino acid peptide derived from bee venom of Apis mellifera, can exert toxic or inhibitory effects on many types of tumor cells. Here we report that melittin can induce apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 46 publications
9
103
1
4
Order By: Relevance
“…8,26 On the one hand, Mucha et al 28 observed that JNK inhibition sensitizes hepatocellular carcinoma cells to TRAIL, but other groups have shown that JNK activation sensitizes hepatocellular carcinoma and breast cancer cells to TRAIL-induced apoptosis. 29,30 Our results would rather support the second conclusion because apoptosis induced by oxaliplatin/TRAIL combination was strongly suppressed by JNK inhibition or knockdown. Several studies have focused on the implication of JNK activation in apoptosis induced by the mitochondrial pathway.…”
Section: Discussioncontrasting
confidence: 37%
“…8,26 On the one hand, Mucha et al 28 observed that JNK inhibition sensitizes hepatocellular carcinoma cells to TRAIL, but other groups have shown that JNK activation sensitizes hepatocellular carcinoma and breast cancer cells to TRAIL-induced apoptosis. 29,30 Our results would rather support the second conclusion because apoptosis induced by oxaliplatin/TRAIL combination was strongly suppressed by JNK inhibition or knockdown. Several studies have focused on the implication of JNK activation in apoptosis induced by the mitochondrial pathway.…”
Section: Discussioncontrasting
confidence: 37%
“…Melittin also inhibits Ca 2+ -ATPase in the sarcoplasmic reticulum, suggesting modulation of IC is not just related to cell membrane perturbation [36]. The peptide (1.8-3.5µM) did not alter membrane integrity of HepG2 cells when stained with annexin-FITC/PI dual staining, indicating an apoptotic process rather than necrosis [16]. Further assessment indicated that melittin increased IC followed by activation of a signaling cascade involving CAMKII-TAK1-MKK-JNK/p38.…”
Section: Discussionmentioning
confidence: 90%
“…It increased IC in osteoblast-like cells [32], fibroblasts [33], hepatocytes [16,34] and mast cells [35]. In human osteoblasts, melittin increased IC levels only when calcium was present extracellularly and not from intracellular stores [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations